Peran Jaksa Pengacara Negara Sebagai Perwakilan RSUD Karawang dalam Kasus Wanprestasi - Amri, Qoonitah; Dewi, Sartika; Abas, Muhamad (Universitas Widya Gama Malang, 2025)
The Republic of Indonesia is a state based on law, as affirmed in Article 1, Paragraph (3) of the 1945 Constitution. One of the critical government institutions within this legal framework is the Attorney General's Office, which functions in the judicial authority concerning prosecution and holds various powers as mandated by law. The State Attorney's Office operates under this institution, specifically handling civil matters on behalf of the state. This study aims to identify the role of the State Attorney in handling Case Number 44/Pdt.G.S/2022/PN Kwg and to examine the legal considerations used by the judge in deciding this case. The research employs a normative juridical approach, which, according to Soerjono Soekanto, involves examining library materials or secondary data as the basis for analysis. The findings reveal that the State Attorney can act as a legal representative for the state, as stipulated in Article 30, Paragraph (2) of Law Number 16 of 2004. However, State Attorneys face challenges, one of which is the non-executable nature of some verdicts, often due to the absence of executable assets, execution objects being held by third parties, or the declaratory nature of the verdicts. In Case Number 44/Pdt.G.S/2022/PN Kwg, the judge partially granted the plaintiff's claim. The judge's considerations, based on Articles 1320, 1238, and 1234 of the Indonesian Civil Code, established that the legal agreement between the parties became void due to the negligence of one party. Consequently, the judge concluded that the defendant was in breach of contract (wanprestasi).